DLX3 epigenetically regulates odontoblastic differentiation of hDPCs through H19/miR-675 axis. (June 2019) - Zeng, Li; Sun, Shichen; Dong, Liying; Liu, Yang; Liu, Haochen; Han, Dong; Ma, Zeyun; Wang, Yixiang; Feng, Hailan
Highlights: We explored the mechanism regarding how DLX3 regulates dentin development. Our new finding is that mutant DLX3 significantly inhibits hDPCs odonto-differentiation through H19/miR-675 axis. Our finding provides an explanation how mutant DLX3 epigenetically alters H19 methylation contributes to dentin hypoplasia in TDO syndrome. Abstract: Objectives: A novel mutation (c.533 A > G; Q178R) in DLX3 gene is responsible for Tricho-Dento-Osseous (TDO) syndrome. As one of features of TDO syndrome is dentin hypoplasia, we explored the mechanism regarding dentin defects in TDO syndrome. Design: hDPCs were obtained from the healthy premolars, stably expressing hDPCs were generated using recombinant lentiviruses. Quantitative methylation analysis, DNMT3B activity, CHIP, and evaluation of odonto-differentiation ability of hDPCs assays were performed. Results: Novel mutant DLX3 (MU-DLX3) significantly inhibited the expression of long non-coding RNA H19 and resulted in hyper-methylation of H19 in MU group, rescue studies showed that up-regulation the expression of H19 and demethylation of H19 in MU group were able to rescue the effect of MU-DLX3. Subsequently, miR-675, encoded by H19, was also able to rescue the above effects of MU-DLX3. Thus, we proposed that MU-DLX3 regulated odontoblastic differentiation of hDPCs through H19/miR-675 axis. Through CHIP and DNMT3B activity assays disclosed the underlying mechanism by which MU-DLX3 altered H19 expression and methylation status in MU group by increasing H3K9me3 enrichment and DNMT3B activity. Conclusions: Our new findings, for the first time, suggest that MU-DLX3 significantly inhibits hDPCs differentiation via H19/miR-675 axis and provides a new mechanism insight into how MU-DLX3 epigenetically alters H19 methylation status and expression contributes to dentin hypoplasia in TDO syndrome.